Using think-alouds to understand how students balance free speech and inclusion. Issue 1 (2nd January 2021) - Bernstein, Jeffrey L.; Armstrong, Cameron W.
ABSTRACT: We explore student attitudes toward freedom of speech on campus using a think-aloud method, in which students are exposed to source material on a subject and "think aloud" as they work through the controversies. We gain an in-depth picture of how students understand and make judgments about who should and should not be allowed to speak on campus. Utilizing the think-aloud method to examine various cases of invited speakers on campus, we learn that students have difficult times differentiating legal and political reasons for preventing certain campus speakers. We also find that students tend to be more restrictive than a civil libertarian might like, albeit in (usually) internally consistent and sympathetic ways. We conclude by suggesting interventions that could help students better understand the way First Amendment rights are typically adjudicated and balanced against other lofty goals.